Prevalence and factors associated with sepsis and septic shock in oncological patients in intensive therapy - Miriam Maria Mota Silva; Danielle Samara Tavares de Oliveira-Figueiredo; Adilma da Cunha Cavalcanti (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze factors associated with sepsis and septic shock in cancer patients in the Intensive Care Unit. Methods: cross-sectional, retrospective study with a quantitative approach, with a sample of 239 patients in an oncology hospital. Secondary data from medical records were used. The outcome variable was "presence of sepsis and/or septic shock"; and exposures: sex, length of stay, origin, use of invasive procedures and primary tumor site. Descriptive, bivariate analyzes and multiple logistic regression models were performed. Results: the prevalence of sepsis was 95% CI: 14.7-24.7 and septic shock of 95% CI: 37.7-50.3. In the multiple analysis, sepsis and/or septic shock were associated with hospital stay longer than seven days, being from the Emergency Department, presence of invasive procedures and hematological site. Conclusions: sepsis and/or septic shock in cancer patients were associated with clinical characteristics and health care factors.